Dynamics Of Land Acquisition Policy Amidst Local Wisdom Case: Route Deviation Not in Accordance with Planning - Yeni Nurul Kurniawati; Roekhudin Roekhudin; Sari Atmini (Green Publisher Indonesia, 2025)
Land acquisition for infrastructure development often faces complex dynamics, especially when there are changes in the route that are not in accordance with the initial planning. This study examines the route deviation policy in the Peterongan Irrigation Network project in Jombang Regency, which aims to avoid socio-cultural conflicts, especially related to the presence of ancestral graves. A qualitative approach with case study method was used through interviews, observations, and documentation. The research findings indicate that the route realignment carried out remains within the scope of the Location Determination Permit, resulting in land and budget efficiency. However, this change was not followed by complete administrative procedures, such as official map revision and public re-consultation, thereby raising issues of transparency and potential legal risks. Additionally, significant budget revision reflects challenges in public fund management. This study emphasizes the importance of implementing principles of transparency, public participation, and legal compliance in land acquisition so that infrastructure development runs effectively and fairly. Recommendations are provided to strengthen land acquisition governance that is responsive to local wisdom values and legally and financially accountable.